Grow your groceries : 40 hacks for growing plants from supermarket foods - Akeroyd, Simon (DK Publishing, 2025)
"Ever wondered if you could grow plants from the food you buy? Grow Your Groceries shows you how. Discover 40 simple, fun hacks to try - no gardening experience needed, just a window sill and a recycled container. Raise tomato plants from tomato slices. Collect strawberry seeds for endless strawberry plants. Pick salad leaves from beetroot tops. Split teabags for flowering camomile. Grow fresh cobs from popcorn kernels. So don't throw away your melon seeds and spring onion trimmings, save them to grow new plants instead!"--Provided by publisher.